2016
DOI: 10.1017/s1366728916000390
|View full text |Cite
|
Sign up to set email alerts
|

The future of code mixing research: Integrating psycholinguistic and formal grammatical theories

Abstract: Our keynote article “Coactivation in bilingual grammars: A computational account of code mixing” (Goldrick, Putnam & Schwarz) aimed to provide a framework that would begin to unify psycholinguistic and formal grammatical approaches to code mixing. We situated our account within a large body of psycholinguistic and phonetic evidence suggesting that, under many conditions, multiple representational elements simultaneously occupy (to varying degrees) a single position within a linguistic structure. The presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 9 publications
(8 reference statements)
1
11
0
Order By: Relevance
“…This establishes the result in (21). In vℒ + V ≡ vℒ + Lv, ℒ will surface: the output will be v.ℒ v; mapping ① vℒ + V → v.ℒv; peti(t) + ami → .pø.ti.ta.mi.…”
Section: A Meta-analysis Of the Liaison Analysissupporting
confidence: 60%
See 1 more Smart Citation
“…This establishes the result in (21). In vℒ + V ≡ vℒ + Lv, ℒ will surface: the output will be v.ℒ v; mapping ① vℒ + V → v.ℒv; peti(t) + ami → .pø.ti.ta.mi.…”
Section: A Meta-analysis Of the Liaison Analysissupporting
confidence: 60%
“…Of central importance in that work is the complex interaction between crucial gradience and strong structure-sensitivity. Some initial applications of this work have accounted for gradience in sound structure errors in speech production [18] and the distribution of gradient structures in multilingual code switching [19] [21].…”
Section: General Overview Of Gscmentioning
confidence: 99%
“…), grammar systems undergoing some form of restructuring can take various paths. 2 They may show restructuring due 2 Probabilistic models such as Emergent Grammars (MacWhinney 2015), Harmonic Grammar (HG; Legendre et al 1990;Pater 2009;McCarthy and Pater 2016) and Gradient Symbolic Computation (GSC; Goldrick et al 2016aGoldrick et al , 2016b to cross-linguistic effects in the integration of syntactic features, lexical items, and discourse-related phenomena (Sánchez 2003(Sánchez , 2004Leal et al 2014), or they may show cross-linguistic influence at the morphosyntactic and syntactic levels (Cuza 2013).…”
Section: Differential Access In Heritage Grammarsmentioning
confidence: 99%
“…As pointed out by an anonymous reviewer, other studies have shown that bilinguals simultaneously activate elements from both languages, and a model has been proposed in which multiple elements may be present simultaneously in a position in the linguistic structure, referred to as co-activation or blends. See [57,58] for discussion of such an analysis.…”
Section: The Structure Of (American) Norwegian Noun Phrasesmentioning
confidence: 99%